Réponses

  • Utilisateur Brainly
2014-09-07T16:37:45+02:00
(2x + 1)(3x - 5) - (3x - 7)(3x - 7) = 0
6x² - 10x + 3x - 5 - 9x² + 21x + 21x - 49 = 0
- 3x² + 35x - 54 = 0
3x² - 35x + 54 = 0

Δ= b² - 4ac
Δ= (- 35)² - 4 x 3 x 54
Δ = 1 225 - 648
Δ = 577

On a Δ > 0 donc l'équation a deux racines réelles distinctes.

\boxed{\boxed{x_1_,_2= \frac{-b\pm \sqrt{\Delta} }{2a} }}



 x_1= \frac{35- \sqrt{577} }{6}  \\  \\ x_2= \frac{35+ \sqrt{577} }{6}
2014-09-07T16:44:36+02:00
Bonjour

Equation

(2x+1)(3x-5) - (3x-7)(3x-7) = 0 

(2x + 1)(3x - 5) - (3x - 7)(3x - 7) = 0
6x² - 10x + 3x - 5 - 9x² + 21x + 21x - 49 = 0
- 3x² + 35x - 54 = 0



Δ= (-35)² - 4 x -3 x -54
Δ = 1 225 - 648
Δ = 577


x1 = (-35 - V577) / 6
x2 = (-35+V577) /6